Lived Experiences of End Stage Renal Disease Patients Undergoing Continuous Ambulatory Peritoneal Dialysis Therapy - M. Hanif Prasetya 'Adhi; Yanny Trisyani; Etika Emaliyawati (Faculty of Nursing Universitas Padjadjaran, 2021)
End stage renal disease (ESRD) is a serious chronic disease that resulted from complications of chronic renal failure and a final diagnosis that requires treatment modalities such as dialysis or continuous ambulatory peritoneal dialysis (CAPD). However, CAPD is rarely selected as renal replacement therapy by ESRD patients in Indonesia. Therefore, the phenomenon associated with patients undergoing CAPD is unclear, especially in Indonesia. The purpose of this study was to explore the lived experiences of ESRD patients undergoing CAPD therapy. The research method employed qualitative descriptive phenomenology. The participants in this study were 10 ESRD patients with CAPD. Data collection utilized semi-structured interviewed and data was analyzed using the Colaizzi approach. The result of the study was explained through 6 themes. These are: 1) Condition improved with CAPD, 2) Freedom of activity, 3) Between feeling better and bored 4) Health is increased, 5) It is sustained life, 6) Resignation to accept illness. In conclusion, the patients with CAPD felt significant positive changes in their life and CAPD is considered life-sustaining for the participants, as the majority of the symptoms was decreased significantly. Therefore, the partisipants felt their conditions improved better. The unpleasant sides of CAPD are feeling bored. The support of the family is important as it produced strength and passion for patients in undergoing CAPD